KEMAMPUAN PENALARAN SPASIAL SISWA SMPN 2 PRAYA BARAT DAYA - Akbar, Khairul (Media Pendidikan Matematika, 2019)
Having good spatial reasoning skills supports a person's success in the STEM field. Spatial reasoning in mathematics is found in geometry. Students' abilities in geometry at SMPN 2 Praya Barat Daya are very low. The purpose of this study was to determine the process of thinking students on spatial reasoning. Spatial reasoning in this study is limited to the constructs of spatial visualization, mental rotation, and spatial orientation. This type of research is descriptive qualitative with a type of eksploratory research. The research subjects were selected 3 students with high, medium, and low mathematical abilities. The main instrument is the researchers himselfs and other instruments are written tests of spatial reasoning and interviews. The results showed: (1) students with high mathematical abilities had better spatial visualization abilities than other students, the three students were not able to use mental rotation skills properly, and the three students were able to use the ability of spatial orientation well, (2) the thinking process of students with high mathematical abilities in spatial visualization was done through reflecting objects, while other students through following the position of the object, in mental rotation the three students did not look too closely at the part of the object being rotated, andÂ  spatial orientation was done bystudent through positioning themselves as objects.